Antimicrobial activity of four Valeriana L. (Caprifoliaceae) crude extracts, endemic species of the Venezuelan Andes - Rondon, Maria Eugenia (2018)
Valeriana L. genus is represented in Venezuela by 16 species, 9 of these are endemic of Venezuelan Andes growing in high mountains at 2800 masl. In this investigation, four species were analyzed in order to determine the main secondary metabolites and antimicrobial activity of extracts obtained from aerial parts of Valeriana parviflora, V. rosaliana, V. triplinervis and V. phylicoides. Alkaloids, flavonoids, tannins, sterols, triterpenoids and saponins were qualitatively observed in all methanolic extracts tested. The color intensity or a precipitate formation was used as analytical response to these tests. Antimicrobial activity was evaluated against Gram positive, Gram negative bacterial strains and yeast, using disc diffusion method. N-hexane extracts of V. triplinervis and V. rosaliana showed the highest efficiency against Staphylococcus aureus, exhibiting inhibition zones of 16 mm and 15 mm; MIC (Minimal Inhibition Concentration) values were observed at 116 mg/mL and 150 mg/mL, respectively. Dichloromethane and methanolic extracts of V. triplinervis and methanolic extract of V. rosaliana showed a rather moderate activity (MIC between 200 to 316 mg/ml) but a very weak antibacterial activity was observed in V. phylicoides and V. parviflora extracts (MIC > 420 mg/mL). None of the extracts assayed in this investigation showed any activity against Candida albicans and Candida krusei. Statistical analysis showed no significant differences on the different polarity extracts assayed with respect to antimicrobial activity against S. aureus (P > 0.10), however it was observed significant differences between the Valeriana species analyzed (P < 0.10) in relation to the minimal inhibitory concentration (MIC).